Comparison of Physical Fitness and Body Composition Components in Parkour Practitioners Based on Years of Training - Solano Chamorro, Michael (2017)
The purpose of the study was to compare physical fitness and anthropometric components in parkour practitioners and find out how years of training influence these variables. Methodology: A total of 18 males participated in the study, who were divided in 3 groups based on years of training. Measurements were taken of anthropometric variables: height, weight, skeletal muscle mass, fat mass, body mass index, as well as physical fitness variables: flexibility (hamstring extensibility), power in upper and lower limbs and resistance to explosive force. One-way ANOVA was used for the independent groups and the Tukey’s post hoc normality test was used to determine significant differences, at an alpha level of p <.05. Results: no significant differences were found between the groups in any of the anthropometric variables.  However, significant differences were found in the component physical fitness, bipodal horizontal jump (P = .02), CMJUL (Countermovement Jump applied to upper limbs) (p = .01) and CMJ (Countermovement Jump) (p = .00), being the group with more years of training the highest of the three. Conclusions: results showed that body composition in parkour athletes was not influenced by years of practice. However, differences found in physical fitness variables, years of training seem to have effects on performance, especially in the physical power of the lower and upper train.